Pengukuran Kuantitas dan Kualitas Penerapan Konsep Kampus Hijau - Kohar, Nanang; Sofyanti, Devy; Hasibuan, Safril; Suntoro, Bambang (JURNAL ADMINISTRASI KANTOR; Vol 13 No 1 (2025): Jurnal Administrasi Kantor (Juni 2025), 2025)
This research aims to measure the success of implementing the green campus concept through both quantitative and qualitative approaches. The quantitative approach analyzes measurable data on sustainable practices such as energy reduction, carbon emissions, and waste management. Meanwhile, the qualitative approach involves in-depth interactions with key stakeholders to understand perspectives and behavioral changes in the implementation process. The research uses a sample of 200 respondents from June to August 2024, with multiple linear regression analysis, questionnaire distribution, interviews, and literature studies. The data are then processed using SPSS and AMOS Analysis V. 25. The results of the research show that the quantitative analysis reveals the impact of sustainable practices, while the qualitative analysis explores perspectives and challenges faced. The combination of these two approaches provides a holistic view of the success of the green campus concept. These findings serve as a basis for better decision-making to promote sustainability efforts on campus and enhance overall sustainability, where measuring the success of the green campus concept through both qualitative and quantitative approaches has a significant positive impact. Keywords : Quantity, Quality, Green Campus